SIMULIAKRAI NIEKUR NEBUVO IŠĖJĘ. - Sabolius, Kristupas (Problems / Problemos, 2011)
This paper focuses on the problem of simulacra avoiding the direct reading of Baudrillard's work. Rreconsidering original meaning of the term in the ancient texts and drawing the parallels with phenomenological contexts, it strives to gain the new meaning for the juxtaposition between the reality and illusion (or imagination). The concept of Eepicurean and Stoic Phantasia contained the intrinsic intertwining of reality and simulacra, due to which reality ab origine presented itself as a correlate of fiction and truth. The similar structure could be identified in the eidetic way of knowledge, which phenomenology finds through the task of Fulfillment (Erfüllung). Aaccording to this research, by virtue of eidetic seeing based on imaginings, the dynamic homogeneity of the conciosousness and the world can be re-established. This tendency is also endorsed by the analysis of so-called 'weak phantasmata', ellucidating the active role which imagination takes in every perception.